Water-Use Efficiency and Growth Capacity of Two Amaryllidaceae Species under Three Different Water Regimes - Vidal, P. (2013)
Habranthus tubispathus and Rhodophiala bifida are two Amaryllidaceae species native toArgentina showing a potential interest for using as garden plants. Both species show a different distribution, since H. tubispathus is usually found in more xeric habitats than R. bifida . The objective of the present work was to study the growth capacity and the water use efficiency at leaf and plant level of R. bifida and H. tubispathus under different water regimes. Bulbs of both species were grownin pots under greenhouse conditions during spring and subjected to three different water regimes: field capacity, 60% of field capacity and 40% of field capacity. During the first ten days, all plants were grown under well watered conditions. Thereafter, water stress treatments were applied for a period of six weeks. Variations in plant water use efficiency (WUE p ), biomass production and gas exchange parameters, including water use efficiency at leaf level (both A/g, intrinsic water use efficiency, and A/E, instantaneous water use efficiency), were analyzed. http://aladee.org/Both species showed similar biomass production regardless the water regime. By contrast, Rhodophiala presented a higher WUE p than Habranthus and both species showed a higher WUE p under water stress (up to4 gdry matter l-1 in Rhodophiala and up to 2.7 g dry matter l -1 in Habranthus ) than under field capacity (1.6 g dry matter l - 1 in Rhodophiala and 1.0 gdry matter l-1 in Habranthus). Similar results were observed when WUE at leaf level was analyzed. The correlation between WUEp and A/g was positive and significant when both species were considered. By contrast, this correlation was not significant for each single species, suggesting the difficulties to estimate WUE p from gas exchange measurements.